2015
DOI: 10.1111/ics.12232
|View full text |Cite
|
Sign up to set email alerts
|

Application of microencapsulated essential oils in cosmetic and personal healthcare products – a review

Abstract: Synopsis Nowadays, the consumers around the world are increasingly focused on health and beauty. The renewed consumer interest in natural cosmetic products creates the demand for new products and reformulated others with botanical and functional ingredients. In cosmetic products, essential oils (EOs) play a major role as fragrance ingredients. They can optimize its proprieties and preservation, as well as the marketing image of the final product. Microencapsulation of EOs can protect and prevent the loss of vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
160
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(176 citation statements)
references
References 87 publications
1
160
0
3
Order By: Relevance
“…Eucalyptus is a rich source of polyphenols, terpenoids, eucalyptol and cineole (GHiSalbeRti 1996, laMbeRt et al 2001, dey & MitRa 2013. Essential oils from E. camaldulensis are used to produce soaps, detergents, lotions and perfumes and also to flavour foods and beverages (caRvalHo et al 2016). The plant has also an antimicrobial potential against gram-positive bacteria (neelaM et al 2014) and anti-inflammatory (Pino et al 2002), antitermitic (SiRaMon et al 2009), larvicidal and mosquito repellent effect (batiSH et al 2008, neRio et al 2010, as well as antioxidative and antiradical properties (SiRaMon & oHtani 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus is a rich source of polyphenols, terpenoids, eucalyptol and cineole (GHiSalbeRti 1996, laMbeRt et al 2001, dey & MitRa 2013. Essential oils from E. camaldulensis are used to produce soaps, detergents, lotions and perfumes and also to flavour foods and beverages (caRvalHo et al 2016). The plant has also an antimicrobial potential against gram-positive bacteria (neelaM et al 2014) and anti-inflammatory (Pino et al 2002), antitermitic (SiRaMon et al 2009), larvicidal and mosquito repellent effect (batiSH et al 2008, neRio et al 2010, as well as antioxidative and antiradical properties (SiRaMon & oHtani 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies have demonstrated that chemosensitization of microorganisms by essential oils or their isolated compounds improved the efficacy of commercial antifungal agents . Essential oils are an important group of plant secondary metabolites used on a large scale in the cosmetic, food and pharmaceutical industries due to their related biological effects . Therefore, these substances can be an alternative to be used in combination with antifungals agents, as they are associated with antimicrobial, anti‐inflammatory and antioxidant activities …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, EOs have a short life, as they are volatile and reactive in the presence of light, heat, moisture and oxygen. Several researchers have investigated alternatives to overcome these challenges, and microencapsulation has been considered as one of the most effective techniques . Moreover, due to the presence of known potential allergens, some EOs may show skin sensitization such as contact irritation, allergy and phototoxicity/photoallergy .…”
Section: Introductionmentioning
confidence: 99%